Simulation of Spot Welding Robot for Automotive Manufacturing Application - Karthickraj, N.; Thamotharan, C.; Naveenchandran, P. (International Journal of Psychosocial Rehabilitation, 2018)
One of the most important applications of industrial robots is spot welding which is used in high production applications mostly in automotive industries where mass production is required. The speed, precision, efficiency and the resulting cost reduction due to mass production are well accepted and well documented advantages of automation of spot welding process using robots. In order to meet the new challenges of increased global competition, manufacturers are forced to seek new technologies for improved production and cost reduction. Such cost cutting efforts can only be achieved by improving the offline programming method. Offline programming is one of the most crucial parts of modern automotive manufacturing process. The whole process design of the robotic spot welding is not simple and includes CAD design of the part, shape and complexity of the parts which needs to be spot weld, design of the robot work cell, design and selection of spot weld gun, required production rate, offline programming tool, robot calibration, work cell calibration, work piece positioner design etc. In this report an approach to implement the offline programming of robot based on simulation software with the process knowledge of car-body in white was proposed and partially developed. Some common problems such as motion simulation, collision detection and calibration can be partly solved by this approach. The results from offline programming (robotic simulation) show that the new welding layout is capable of achieving the manufacturer’s target. The implementation of RSWS for automotive application is reasonable because of efficiency, accuracy and cost effective.